Mark's basic medical biochemistry : a clinical approach - Lieberman, Micheal; Marks, Allan D.; Peet, Alisa (Wolter Kluwer/Lippincott Williams & Wilkins, 2013)
"This core textbook helps medical students bridge the gap between biochemistry, physiology, and clinical care. The strength of Mark's Basic Medical Biochemistry is that it starts with the patient--the metabolic and nutritional needs of the human body (easy for students to understand)--as opposed to explanations of complex chemical theory. Mark's Basic empahsizes clinical correlations throughout the text and links biochemical concepts to physiology and pathophysiology, using patient vignettes as the context. These specific and memorable mock patient cases are followed throughout the chapter to pose questions, illustrate core concepts, and help students remember and apply biochemical priniciples within the context of clinical practice"--Provided by publisher.